Internal load of soccer goalkeepers during the improvement of selected game activities - Babic, M.; Holienka, M.; Mikulic, M. (Journal of Physical Education and Sport, 2018)
The main topic of our research was to determine the internal load of goalkeepers in the phase of improving game activities. We focused on the analysis of the achieved heart rate values. In this way, we wanted to extend the knowledge of the impact of the various small sided games (SSG) on the internal load on soccer goalkeepers, there by supporting the effort to improve the youth training process. We assumed the goalkeepers reached a significantly different level of heart rate, terms of their individual assumptions and load variability in different small sided games. Four goalkeepers (U16, U17) internal load were analysed by POLAR Team PRO. To determine statistical significance, we used the Wilcoxon T-test. Then we calculated Cohen r (effect size) and the significance test of two relative values. The selected level of statistical significance was p.0.05. We found different mean heart rate values in selected small sided games, so we confirmed the assumption at least logically. At the same time, we confirmed that both small sided games had the required impact on adaptive changes to the goalkeepers body.